AC conductivity and dielectric properties of B2O3-WO3-TeO2- Li2O glasses. (2018) - Edukondalu, Avula; Venkatesham, N.; Keerthi Devi, D.; Rahman, Syed; Siva Kumar, K.
Abstract: Glass with composition (20-x)B2 O3 -10WO3 -70TeO2 - xLi2 O with 0 ≤ x ≤ 20 have been prepared by conventional melt quench technique. The impedance spectroscopy technique is employed on these samples and the data are analyzed using Cole-Cole type impedance response function. The AC conductivity behavior of the present glasses has been investigated in the frequency range from 100Hz to 1MHz and as a function of temperature the measured. Ac data are analyzed using the power law to explain the observed depressive behavior of the electrical conductivity. The temperature and composition dependence scaling behavior in the AC conductivity are satisfactorily explained by scaling the AC conductivity σ′(ω) by hopping frequency ωp . The frequency response of dielectric constant and dielectric loss tanδ as a function of temperature were studied.